Protective and resilience factors to promote mental health among Indigenous youth in Canada: a scoping review protocol. Issue 1 (17th January 2022) - Carrier, Leah; Shin, Hwayeon Danielle; Rothfus, Melissa A; Curran, Janet A
Abstract : Introduction: Many mental health concerns emerge in adolescence and young adulthood, making this a critical period to initiate early interventions for mental health promotion and illness prevention. Although Indigenous young people in Canada are at a higher risk of mental health outcomes and faced with limited access to appropriate care and resources, they have unique strengths and resilience that promote mental health and wellness. Furthermore, resilience has been described as a 'healing journey' by Indigenous peoples, and interventions that account for the culture of these groups show promise in promoting mental health and wellness. As such, there is a need for innovative mental health interventions for Indigenous youth that transcend the Western biomedical model, use a strengths-based approach, and account for the cultural practices and belief systems of Indigenous peoples. This scoping review aims to explore the resilience and protective factors that promote mental health and wellness for Indigenous youth in present-day Canada with the aim of compiling and summarising the available literature on this topic to date. Methods and analysis: The review will follow Joanna Briggs Institute methodology for conducting scoping reviews. The reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-analyses Extension for Scoping Reviews checklist and guidelines. We will include both published and unpublished grey literature and search the following databases: PubMed, CINAHL, PsycINFO, Education Resources Information Center, Embase and Scopus. The search of all databases was conducted on 26 August 2021. Further, we will use government and relevant Indigenous organisation websites. Two reviewers will independently screen and select the articles and extract the data. Ethics and dissemination: No ethical approval is required for this study. We will share the results through conference presentations and an open-access publication in a peer-reviewed journal. A lay-language report will be created and disseminated to community organisations that work with Indigenous youth.